2020
DOI: 10.1007/s13399-020-00965-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical challenges in biohydrogen production processes from the organic feedstocks

Abstract: The ever-increasing world energy demand drives the need for new and sustainable renewable fuel to mitigate problems associated with greenhouse gas emissions such as climate change. This helps in the development toward decarbonisation. Thus, in recent years, hydrogen has been seen as a promising candidate in global renewable energy agendas, where the production of biohydrogen gains more attention compared with fossil-based hydrogen. In this review, biohydrogen production using organic waste materials through fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(45 citation statements)
references
References 140 publications
0
45
0
Order By: Relevance
“…These techniques are absorption, microalgae, membrane separation, adsorption and cryogenics ( Fig. 4) (Osman et al 2020a;Li et al 2012a).…”
Section: Co 2 Separation Methods From Flue Gas In Combustion Capture mentioning
confidence: 99%
See 2 more Smart Citations
“…These techniques are absorption, microalgae, membrane separation, adsorption and cryogenics ( Fig. 4) (Osman et al 2020a;Li et al 2012a).…”
Section: Co 2 Separation Methods From Flue Gas In Combustion Capture mentioning
confidence: 99%
“…CO 2 is then undergoing compression and liquefication for storage or transportation purposes at low power requirements. Moreover, it promotes the production of H 2 as a fuel that can be used in fuel cells (after further purification), transportation or as a building block in the production of value-added chemicals (Osman et al 2020a). Another big benefit of the pre-combustion route is the flexibility of the outputs where H 2 production or power generation can easily be switched according to the demand.…”
Section: Pre-combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major challenging factor for photofermentative hydrogen production is the efficiency differences at which light is utilized by phototrophs under different magnitude of light concentrations [34] as recently reported that low-intensity electromagnetic field of extremely high frequencies affects hydrogen production by Rhodobacter sphaeroides [35]. This experience made the process to be a bit daunting to navigate through finding a suitable intensity condition in addition to alternative sources of light [36].…”
Section: Light Source and Light Conversion Efficiencymentioning
confidence: 99%
“…The physical and chemical environments of the earth show a wide variation in which microorganism lives in almost all places. Depending on the temperature, the microbes living in these environments can be divided into three classes namely thermophiles (45–65 °C), mesophiles (25–45 °C), and psychrophiles (0–25 °C) 1 . Thermophiles operate their biochemical machinery at boiling temperatures that are detrimental to mesophilic microbes 2 4 .…”
Section: Introductionmentioning
confidence: 99%